A Review of Unconventional Citation Metrics for Scientific Publications - Shikha Gupta; Sakshi Wadhwa; Samarth Gupta (MASI Mandiri Edukasi, 2025)
Citation metrics play a crucial role in evaluating the impact and significance of scientific publications within the research community. Among the widely recognised indicators are the journal impact factor and the h-index, the latter often used to evaluate and rank academic conferences. Despite the prominence of these metrics, many scholars remain unfamiliar with a range of alternative measures available for assessing scholarly output. This review examines various citation-based metrics employed to assess scientific publications. Although some of these metrics offer distinct advantages, they have not yet been widely adopted by journals, funding bodies, or researchers. This review aims to provide a detailed overview of lesser-known citation indicators and to support researchers in making more informed evaluations of academic influence and research quality.